Neuromuscular electrical stimulation improves exercise tolerance in patients with advanced heart failure on continuous intravenous inotropic support use—randomized controlled trial. (January 2018) - Forestieri, Patrícia; Bolzan, Douglas W; Santos, Vinícius B; Moreira, Rita Simone Lopes; de Almeida, Dirceu Rodrigues; Trimer, Renata; de Souza Brito, Flávio; Borghi-Silva, Audrey; de Camargo Carvalho, Antonio Carlos; Arena, Ross; Gomes, Walter J; Guizilini, Solange
Objective: To evaluate the impact of a short-term neuromuscular electrical stimulation program on exercise tolerance in hospitalized patients with advanced heart failure who have suffered an acute decompensation and are under continuous intravenous inotropic support. Design: A randomized controlled study. Subjects: Initially, 195 patients hospitalized for decompensated heart failure were recruited, but 70 were randomized. Intervention: Patients were randomized into two groups: control group subject to the usual care ( n = 35); neuromuscular electrical stimulation group ( n = 35) received daily training sessions to both lower extremities for around two weeks. Main measures: The baseline 6-minute walk test to determine functional capacity was performed 24 hours after hospital admission, and intravenous inotropic support dose was daily checked in all patients. The outcomes were measured in two weeks or at the discharge if the patients were sent back home earlier than two weeks. Results: After losses of follow-up, a total of 49 patients were included and considered for final analysis (control group, n = 25 and neuromuscular electrical stimulation group, n = 24). The neuromuscular electrical stimulation group presented with a higher 6-minute walk test distance compared to the control group after the study protocol (293 ± 34.78 m vs. 265.8 ± 48.53 m, P < 0.001, respectively). Neuromuscular electrical stimulation group also demonstrated a significantly higher dose reduction of dobutamine compared to control group after the study protocol (2.72 ± 1.72 µg/kg/min vs. 3.86 ± 1.61 µg/kg/min, P = 0.001, respectively). Conclusion: A short-term inpatient neuromuscular electrical stimulation rehabilitation protocol improved exercise tolerance and reduced intravenous inotropic support necessity in patients with advanced heart failure suffering a decompensation episode.